Lipoblastoma in children: A case series - Tezazu Teffera Tekle; Metasebia W. Abebe (Elsevier, 2023)
Introduction: Lipoblastoma is a rare benign mesenchymal tumor of embryonic fat that occurs almost exclusively in infants and children. It accounts for less than 1% of childhood neoplasms and is found in slightly higher frequency in males compared to females. Lipoblastomas most commonly occur in the extremities and show variable rates of growth. Surgical excision is the treatment of choice and has an excellent prognosis although recurrences are possible. Case presentation: We report two cases of lower extremity lipoblastoma at 7 and 8 years of age. Both patients presented with a slow-growing painless mass over the thigh with no limitation in the range of motion of the joints of the affected limb. Plain films showed well-demarcated soft tissue masses. Cytological examination was suggestive of lipoblastoma which was later confirmed by histopathology examination. Complete surgical excision with meticulous dissection and preservation of vital neurovascular structures was done in both cases. No recurrence has been observed after 5 years of follow-up. Conclusion: Lipoblastomas should be considered as a possible diagnosis in older children presenting with a solid slow-growing soft tissue mass.